Solar-driven methanol-to-synthesis gas catalyst and preparation method thereof
Through solar-powered methanol-made synthesis gas catalyst, the combination of active components is used to form a mesoporous structure, solving the problems of high energy consumption and carbon emissions under fossil resource dependence, and achieving efficient and stable synthesis gas generation and low-carbon chemical raw materials supply.
Patent Information
- Application Number
- CN202411360939.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-31
AI Technical Summary
The existing industrial synthesis gas preparation methods rely on fossil resources, resulting in high energy consumption and carbon emissions, and the reaction conditions are harsh, making it difficult to achieve green and renewable chemical raw materials supply.
Develop a solar-powered methanol-made synthesis gas catalyst, through the combination of active components such as Al, Cu, Ni, Zn, Zr and its oxides, and use the thermal solvent method to induce self-assembly to form a mesoporous structure composite metal oxide catalyst , use solar energy to efficiently convert methanol into synthesis gas under mild conditions, and regulate the H2/CO molar ratio within the range of 2-3.4.
The synthesis gas generation with high selectivity and high yield rate is achieved, and the catalyst has good reusability and stability, which significantly reduces energy consumption and carbon emissions, and meets the needs of green chemical raw materials.
Smart Images

Figure CN119215880A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and in particular relates to a solar-driven methanol-to-syngas catalyst and a preparation method thereof. Background Art
[0002] Synthesis gas is a mixed gas with hydrogen and carbon monoxide as the main components. It is an important chemical raw material and plays a very important role in the chemical industry. For example, synthesis gas can be used to prepare chemical products such as ammonia, urea and methanol through catalytic reaction. Synthesis gas can also be used to prepare liquid fuels such as diesel and gasoline through Fischer-Tropsch synthesis. At the same time, synthesis gas can also be used as fuel gas and is a high calorific value energy source (Catalysis today, 2000, 63 (2-4), 159-164. Catalysis today, 2002, 71 (3-4), 243-247.).
[0003] At present, industrial syngas is mainly produced by steam reforming with fossil resources as raw materials (such as coal and natural gas), which usually requires high reaction temperature (700-1000°C) and pressure (>2MPa), resulting in high energy consumption and carbon emissions. At the same time, the use of non-renewable fossil resources as raw materials also causes a series of environmental pollution and raw material supply security issues (AngewandteChemie International Edition, 2024, e202405904.). Therefore, it is very important and urgent to develop green and efficient syngas production technology using renewable resources as raw materials.
[0004] Methanol is one of the most common and readily available bulk chemicals. In 2021, the global total methanol production was about 160 million tons. At the same time, it has the characteristics of high hydrogen storage capacity, high energy density, low carbon content, and being liquid at normal temperature and pressure (easy to store and transport). In addition, methanol can be prepared by reducing CO2 with green electricity converted from renewable energy (such as solar energy and wind energy), or it can be produced by biomass refining, and has good renewability. Therefore, it has an advantage as a raw material for preparing synthesis gas. Photocatalysis uses inexhaustible sunlight as the driving energy for the reaction, and has the advantages of being green and having mild reaction conditions, which has attracted widespread attention from researchers. The preparation of synthesis gas from photocatalytically renewable methanol is of great significance to the green and renewable preparation of synthesis gas. At the same time, it has important environmental value for reducing energy consumption and carbon emissions in the preparation process and helping to achieve the goals of "carbon peak and carbon neutrality". Summary of the invention
[0005] The purpose of the present invention is to provide a solar-driven methanol-to-syngas catalyst, the preparation method of the catalyst is simple and the raw materials are cheap and easily available. The prepared catalyst exhibits high synthesis gas activity under a simulated sunlight irradiation reaction. At the same time, by regulating the concentration of methanol, the H2 / CO molar ratio can be regulated within the range of 2-3.4.
[0006] The technical solution adopted by the present invention to solve its technical problem is:
[0007] A solar-driven methanol-to-syngas catalyst is composed of active components and does not require a carrier. The active components are Al and Al oxides, Cu and Cu oxides, Ni and Ni oxides, Zn and Zn oxides, and Zr and Zr oxides. The molar ratio of the active component elements Al:Cu:Ni:Zn:Zr is 1:0.5-1.5:0.5-1.5:0.5-1.5:0.5-1.5.
[0008] The present invention develops a highly active and stable non-precious metal catalyst, which uses solar energy as the only input energy to efficiently convert methanol into synthesis gas under mild conditions, and exhibits high synthesis gas selectivity and good catalyst reusability.
[0009] A method for preparing a solar-driven methanol-to-syngas catalyst according to the present invention comprises the following steps:
[0010] Step 1: Dissolve the calculated amount of metal source in a solvent and stir thoroughly at room temperature until the solution becomes clear;
[0011] Step 2: dissolving the organic ligand in the solution obtained in step 1, and stirring thoroughly at room temperature until the solution becomes clear;
[0012] Step 3: Transfer the solution obtained in step 2 to a hydrothermal reactor and crystallize at 150°C-170°C for 10h-14h;
[0013] Step 4: Filter the solution obtained in step 3 at room temperature, and wash the solid powder with a detergent to remove impurities to obtain a precursor;
[0014] Step 5: Transfer the precursor obtained in step 4 to an evaporating dish and dry it at a temperature of 60°C-70°C to obtain a precursor solid powder;
[0015] Step 6: Move the precursor solid powder left after drying in step 5 into a crucible, and place it in a muffle furnace and calcine it at 700℃±50℃ for 4h-5h with a heating rate of 2-4℃ / min to obtain a solar-driven methanol-to-syngas catalyst.
[0016] Preferably, the Al source is aluminum nitrate, the Cu source is copper nitrate, the Ni source is nickel nitrate, the Zn source is zinc nitrate, the Zr source is zirconium nitrate, the solvent is isopropanol, the organic ligand is glycerol, and the detergent is one or more of anhydrous ethanol, anhydrous methanol or water.
[0017] Preferably, the crystallization method in step three is: transferring the obtained solution to a hydrothermal reactor, and then moving it into an oven, setting the temperature to 160° C., and the crystallization time to 12 h.
[0018] Preferably, the precursor drying method in step 4 is: transferring the obtained precursor to an evaporating dish, and moving it into an oven, setting the temperature to 65° C., and drying time to 14 h.
[0019] Preferably, the calcination method of the precursor solid powder in step five is: the obtained precursor solid powder is moved into a crucible, and then into a muffle furnace, the temperature is set to 700°C, the calcination time is 4h, and the heating rate is 4°C / min.
[0020] An application of the catalyst of the present invention in solar-driven methanol production of synthesis gas, more specifically, in the application, a 300W xenon lamp simulating sunlight is used as the light source in the reaction.
[0021] An application of the catalyst of the present invention in solar-driven methanol production of synthesis gas, wherein the reaction conditions for solar-driven methanol production of synthesis gas are: the reaction light intensity is 3.5-7.5W / cm 2 , the reaction pressure is one atmosphere, and the methanol concentration is 5-24.5 mol / L.
[0022] The catalyst preparation of the present invention adopts a hot solvent method to induce a self-assembly pathway to synthesize a solar-driven methanol-to-syngas catalyst. It should be particularly noted that the solvent isopropanol and the organic ligand glycerol in the method of the present invention play an extremely important role. The ligand glycerol complexes with metal ions to promote the formation of metal glycerol salts (precursor solid powders), while the solvent isopropanol promotes the formation and dispersion of metal glycerol salt microspheres. The absence of both makes it impossible to successfully synthesize the catalyst described in the present invention. The present invention has the following advantages:
[0023] 1. The solar-driven methanol-to-syngas catalyst provided by the present invention is a mesoporous composite metal oxide, which has a simple preparation method and is easy to operate. The raw materials are cheap and readily available non-precious metal salts, and are used for solar-driven methanol-to-syngas;
[0024] 2. The catalyst provided by the present invention is used for producing synthesis gas from methanol driven by solar energy, with a selectivity of up to 99.9% and a synthesis gas production rate of up to 59.3 mol / g / h;
[0025] 3. The solar-driven methanol-to-syngas catalyst provided by the present invention achieves regulation of the H2 / CO molar ratio within the range of 2-3.4 by controlling the concentration of methanol in the methanol-water solution. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can also obtain other drawings based on these drawings without paying any creative work.
[0027] Figure 1 This is a SEM photo of the catalyst product precursor of Example 1;
[0028] Figure 2 This is a SEM photo of the catalyst product of Example 1;
[0029] Figure 3 for Figure 2 Locally enlarged SEM image;
[0030] Figure 4 This is a TEM photo of the catalyst product of Example 1;
[0031] Figure 5 This is a photo of element distribution of the catalyst product of Example 1;
[0032] Figure 6 The process flow chart of preparing the catalyst for producing methanol to synthesis gas driven by solar energy;
[0033] Figure 7 N2 adsorption-desorption curves of the catalyst products of Examples 1-4;
[0034] Figure 8 The pore size distribution diagram of the catalyst products of Examples 1-4;
[0035] Fig. 9 The absorption characteristics of ultraviolet, visible and near-infrared light of the catalyst products of Examples 1-4 are shown;
[0036] Fig.10 The bandgap width diagram of the catalyst products of Examples 1-4;
[0037] Fig.11 This is a stability test chart of the catalyst product of Example 1 after continuous reaction for 12 hours. DETAILED DESCRIPTION
[0038] The technical solution of the present invention is further described in detail below through specific embodiments. It should be understood that the implementation of the present invention is not limited to the following embodiments, and any form of modification or change made to the present invention will fall within the protection scope of the present invention.
[0039] In the present invention, unless otherwise specified, all parts and percentages are by weight, and the equipment and raw materials used can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.
[0040] The catalyst performance was tested using a self-made quartz reactor, and the gas phase product was analyzed using a GC2060 gas chromatograph from Shanghai Minrui Instrument Co., Ltd.
[0041] Example 1
[0042] A method for preparing a solar-driven methanol-to-syngas catalyst, the process flow chart is as follows Figure 6 As shown, the specific steps are as follows:
[0043] Accurately weigh 0.188 g of aluminum nitrate nonahydrate, 0.12 g of copper nitrate trihydrate, 0.145 g of nickel nitrate hexahydrate, 0.215 g of zirconium nitrate pentahydrate, and 0.149 g of zinc nitrate hexahydrate, add them to 34 mL of isopropanol, stir and dissolve thoroughly, and after dissolution, accurately measure 6 mL of glycerol, drip it dropwise into the above solution, stir and dissolve thoroughly until it is clear, transfer the prepared precursor solution to a 100 mL hydrothermal reactor, and place it in a 160 ° C oven for crystallization for 12 h. After sufficient crystallization, filter the solution obtained in the hydrothermal reactor and wash it with anhydrous ethanol to obtain a catalyst precursor (SEM photo as shown in FIG. Figure 1 shown).
[0044] The prepared precursor was transferred to an evaporating dish and placed in a 65°C oven for 14 hours to obtain a precursor powder. The precursor powder in the evaporating dish was transferred to a crucible, which was covered and placed in a muffle furnace. The temperature was set to 700°C, the calcination time was 4 hours, the heating rate was 4°C / min, and the calcination procedure was completed and cooled naturally. A mesoporous composite metal oxide catalyst was obtained (SEM photo as shown in Figure 2 and Figure 3 shown).
[0045] according to Figure 2 and Figure 3 It can be seen that the catalyst synthesized by this method has a porous structure.
[0046] TEM photos of the catalyst products are shown in Figure 4 , the element distribution photos of catalyst products are shown in Figure 5 , combined with Figure 4 and Figure 5It can be seen that the metal Al, Ni, Cu, Zn, Zr and their oxide nanoparticles are evenly distributed, and there is no particle stacking phenomenon. This structure of the catalyst is beneficial to improving the activity and catalytic stability of the active components.
[0047] Example 2
[0048] A method for preparing synthesis gas from methanol driven by solar energy, the specific steps are as follows:
[0049] Accurately weigh 0.188g of aluminum nitrate nonahydrate, 0.12g of copper nitrate trihydrate, 0.145g of nickel nitrate hexahydrate, and 0.215g of zirconium nitrate pentahydrate, add them to 34mL of isopropanol, stir and dissolve thoroughly, and after dissolving, accurately measure 6mL of glycerol, drip it dropwise into the above solution, stir and dissolve thoroughly until it is clear, and move the prepared precursor solution to a 100mL hydrothermal reactor, and put it in a 160℃ oven for crystallization for 12h. After sufficient crystallization, filter the suspension obtained in the hydrothermal reactor and wash it with anhydrous ethanol to obtain a catalyst precursor. Transfer the prepared precursor to an evaporating dish, put it in a 65℃ oven, dry it for 14h, and obtain a precursor powder. Transfer the precursor powder in the evaporating dish to a crucible, cover the crucible, and place it in a muffle furnace. The temperature is set to 700℃, the calcination time is 4h, the heating rate is 4℃ / min, and the calcination procedure is completed and cooled naturally. A mesoporous composite metal oxide catalyst 2 is obtained.
[0050] Example 3
[0051] A method for preparing a solar-driven methanol-to-syngas catalyst, the specific steps are as follows:
[0052] Accurately weigh 0.188g of aluminum nitrate nonahydrate, 0.12g of copper nitrate trihydrate, and 0.145g of nickel nitrate hexahydrate, add them to 34mL of isopropanol, stir and dissolve thoroughly, and after dissolving, accurately measure 6mL of glycerol, drip into the above solution drop by drop, stir and dissolve thoroughly until clear, transfer the prepared precursor solution to a 100mL hydrothermal reactor, and place it in a 160℃ oven for crystallization for 12h. After sufficient crystallization, filter the suspension obtained in the hydrothermal reactor and wash it with anhydrous ethanol to obtain a catalyst precursor. Transfer the prepared precursor to an evaporating dish, place it in a 65℃ oven, dry it for 14h, and obtain a precursor powder. Transfer the precursor powder in the evaporating dish to a crucible, cover the crucible, and place it in a muffle furnace. The temperature is set to 700℃, the calcination time is 4h, the heating rate is 4℃ / min, and the calcination procedure is completed and cooled naturally. Obtain mesoporous composite metal oxide catalyst 3.
[0053] Example 4
[0054] A method for preparing a solar-driven methanol-to-syngas catalyst, the specific steps are as follows:
[0055] Accurately weigh 0.188g of aluminum nitrate nonahydrate and 0.12g of copper nitrate trihydrate, add them to 34mL of isopropanol, stir and dissolve thoroughly, after dissolving, accurately measure 6mL of glycerol, drip into the above solution drop by drop, stir and dissolve thoroughly until clear, transfer the prepared precursor solution to a 100mL hydrothermal reactor, and place it in a 160℃ oven for crystallization for 12h. After sufficient crystallization, filter the suspension obtained in the hydrothermal reactor and wash it with anhydrous ethanol to obtain a catalyst precursor. Transfer the prepared precursor to an evaporating dish, place it in a 65℃ oven, dry it for 14h, and obtain a precursor powder. Transfer the precursor powder in the evaporating dish to a crucible, cover the crucible, and place it in a muffle furnace. The temperature is set to 700℃, the calcination time is 4h, the heating rate is 4℃ / min, and the calcination procedure is completed and cooled naturally. Obtain mesoporous composite metal oxide catalyst 4.
[0056] Example 5
[0057] A method for preparing a solar-driven methanol-to-syngas catalyst, wherein in Example 1, the detergent is replaced by anhydrous methanol from anhydrous ethanol, and other synthesis conditions remain unchanged, to obtain a mesoporous composite metal oxide catalyst 5.
[0058] Example 6
[0059] A method for preparing a solar-driven methanol-to-syngas catalyst, wherein in Example 1, the detergent is replaced by deionized water from anhydrous ethanol, and other synthesis conditions remain unchanged, to obtain a mesoporous composite metal oxide catalyst 6.
[0060] Application Example 1
[0061] 5 mg of the catalyst prepared in Example 1, Example 2, Example 3, and Example 4 were placed in the reactor respectively, the reactor was sealed, vacuumed and introduced with argon gas for five times, the air in the reactor was exhausted, and finally argon gas was introduced. 1 mL of 24.5 mol / L methanol aqueous solution was injected into the reactor under the argon atmosphere. A light source with an intensity of 7.5 W / cm 2 , the reaction started for 5 minutes. After the reaction was completed, the obtained synthesis gas was analyzed by gas chromatography. The specific results are shown in Table 1.
[0062] Table 1 Comparison of the activity of solar-driven methanol-to-syngas catalysts
[0063]
[0064] Application Example 2
[0065] 5 mg of the catalyst prepared in Example 1 was placed in a quartz reactor, the reactor was sealed, vacuumed and introduced with argon, repeated five times, the air in the reactor was exhausted, and finally filled with argon. In the argon atmosphere, 1 mL of a 24.5 mol / L methanol aqueous solution was injected into the reactor. A light source was introduced and the intensity of the light source was adjusted to 3.5 W / cm 2 , 4.5W / cm 2 , 5.5W / cm 2 、6.5W / cm 2 , 7.5W / cm 2 , the reaction started for 5 minutes. After the reaction was completed, the obtained synthesis gas was analyzed by gas chromatography. The specific results are shown in Table 2.
[0066] Table 2 Effect of light intensity on synthesis gas production
[0067]
[0068] Application Example 3
[0069] 5 mg of the catalyst prepared in Example 1 was placed in a quartz reactor, the reactor was sealed, vacuumed and introduced with argon, repeated five times, the air in the reactor was exhausted, and finally filled with argon. Under the argon atmosphere, 1 mL of deionized water and 1 mL of methanol aqueous solution with concentrations of 5 mol / L, 10 mol / L, 15 mol / L, 20 mol / L, and 24.5 mol / L were respectively injected into the reactor. A light source with an intensity of 7.5 W / cm 2 , the reaction started for 5 minutes. After the reaction was completed, the obtained synthesis gas was analyzed by gas chromatography. The specific results are shown in Table 3.
[0070] Table 3 Effect of methanol concentration on synthesis gas production
[0071]
[0072] Application Example 4
[0073] 5 mg of the catalyst prepared in Example 1 was placed in a quartz reactor, the reactor was sealed, vacuumed and argon was introduced, repeated five times, the air in the reactor was exhausted, and finally argon was introduced, and 1 mL of a 24.5 mol / L methanol aqueous solution was injected into the reactor under an argon atmosphere. The heating temperature of the thermocouple was set to 418°C, which was the same as the temperature provided by the light source intensity in Application Example 3, and the reaction was started for 5 minutes. After the reaction was completed, the obtained synthesis gas was analyzed by gas chromatograph, and the specific results are shown in Table 4.
[0074] Table 4 Comparison of thermal reaction activity of methanol to synthesis gas catalysts
[0075]
[0076] Application Example 5
[0077] 5 mg of the catalyst prepared in Example 5 and Example 6 were placed in a quartz reactor respectively, the reactor was sealed, vacuumed and introduced with argon, repeated five times, the air in the reactor was exhausted, and finally argon was introduced. In the argon atmosphere, 1 mL of a 24.5 mol / L methanol aqueous solution was injected into the reactor. A light source with an intensity of 7.5 W / cm 2 , the reaction started for 5 minutes. After the reaction was completed, the obtained synthesis gas was analyzed by gas chromatography. The specific results are shown in Table 5.
[0078] Table 5 Effect of different detergents on syngas production activity
[0079]
[0080] N2 adsorption-desorption experiment
[0081] The specific method of N2 adsorption-desorption test is:
[0082] 1. Weigh about 100 mg of sample and add it into a 9 mm diameter BET sample tube;
[0083] 2. Place the sample tube into the degassing station and degas at 180℃ for more than 8 hours;
[0084] 3. Use QUADRASORB EVO specific surface area and pore size analyzer to conduct N2 adsorption-desorption test on catalyst products.
[0085] The catalyst products obtained in Examples 1-4 were subjected to the above test, and the obtained N2 adsorption-desorption curves were as follows: Figure 7 shown.
[0086] The pore size distribution of the catalyst products obtained in Examples 1-4 is shown in FIG. Figure 8 shown.
[0087] according to Figure 7 , Figure 8 From the data, it can be seen that the adsorption-desorption isotherms of the series of catalysts synthesized by this method show typical type IV isotherms, indicating that the catalyst has a mesoporous structure and the mesopore diameter ranges from 2 to 60 nm.
[0088] according to Fig. 9 , Fig.10 From the data, it can be seen that the series of catalysts synthesized by this method have an increasing ability to absorb sunlight as the number of metal types increases, and the band gap width of the catalyst is gradually decreasing, with the lowest being 1.37ev, which indicates that more sunlight in a longer wavelength band can be utilized.
[0089] according to Fig.11 The data show that the catalyst synthesized by this method has excellent stability.
[0090] As shown in Table 1, the generation rate of syngas gradually increases from low, medium to high entropy of the catalyst, and the H2 / CO molar ratio in the syngas remains unchanged at about 2. As shown in Table 2, with the increase of light intensity, the generation rate of syngas gradually increases, and the H2 / CO molar ratio in the syngas remains unchanged at about 2, indicating that the catalyst synthesized by this method can stably produce syngas with a H2 / CO molar ratio of 2, and its composition ratio is not affected by light intensity and the number of active components. It can be seen from Table 3 that with the increase of methanol concentration in methanol aqueous solution, the selectivity and production rate of synthesis gas gradually increase, and the H2 / CO molar ratio gradually decreases. When the concentration is 5 mol / L, the H2 / CO molar ratio in the synthesis gas is 3.4, and when the concentration is 24.5 mol / L, the H2 / CO molar ratio in the synthesis gas is 2, and the selectivity and production rate reach the maximum, which are 99.9% and 59.3 mol / g / h, respectively. This shows that the H2 / CO molar ratio can be adjusted to 2-3.4 by regulating the concentration of methanol in methanol aqueous solution, and thus has good industrial application prospects; it can be seen from Tables 3 and 4 that the generation rate of photocatalytic synthesis gas is higher than the generation rate of synthesis gas by thermal reaction, indicating that the catalyst synthesized by this method can make full use of sunlight to drive the reaction, which is more energy-saving and environmentally friendly; it can be seen from Table 5 that in the preparation process of the catalyst, different detergents will not affect the catalyst.
[0091] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.
[0092] The above is a detailed introduction to a solar-driven methanol-to-syngas catalyst and a preparation method thereof provided by the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention, and the description of the above embodiments is only used to help understand the method of the present invention and its core idea. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, several improvements and modifications can be made to the present invention, including but not limited to adjusting the molar ratio of each active component, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A solar-driven methanol-to-syngas catalyst, characterized in that: The catalyst is composed of active components and does not require a carrier. The active components are Al and Al oxide, Cu and Cu oxide, Ni and Ni oxide, Zn and Zn oxide, Zr and Zr oxide. The molar ratio of active component elements Al:Cu:Ni:Zn:Zr is 1:0.5-1.5:0.5-1.5:0.5-1.5:0.5-1.
5.
2. A method for preparing a solar-driven methanol-to-syngas catalyst according to claim 1, characterized in that The method comprises the following steps: Step 1: Dissolve the calculated amount of metal source in a solvent and stir thoroughly at room temperature until the solution becomes clear; Step 2: dissolving the organic ligand in the solution obtained in step 1, and stirring thoroughly at room temperature until the solution becomes clear; Step 3: Transfer the solution obtained in step 2 to a hydrothermal reactor and crystallize at 150°C-170°C for 10h-14h; Step 4: Filter the solution obtained in step 3 at room temperature, and wash the solid powder with a detergent to remove impurities to obtain a precursor; Step 5: Transfer the precursor obtained in step 4 to an evaporating dish and dry it at a temperature of 60°C-70°C to obtain a precursor solid powder; Step 6: Move the precursor solid powder left after drying in step 5 into a crucible, and place it in a muffle furnace and calcine it at 700℃±50℃ for 4h-5h with a heating rate of 2-4℃ / min to obtain a solar-driven methanol-to-syngas catalyst.
3. The preparation method according to claim 2, characterized in that: The Al source is aluminum nitrate, the Cu source is copper nitrate, the Ni source is nickel nitrate, the Zn source is zinc nitrate, the Zr source is zirconium nitrate, the organic ligand is glycerol, the solvent is isopropanol, and the detergent is one or more of anhydrous ethanol, anhydrous methanol or water.
4. The preparation method according to claim 2, characterized in that: The crystallization method in step three is: transfer the obtained solution to a hydrothermal reactor, and move it into an oven, set the temperature to 160° C., and the crystallization time to 12 h.
5. The preparation method according to claim 2, characterized in that: The precursor drying method in step 5 is: transfer the obtained precursor to an evaporating dish, and move it into an oven, set the temperature to 65° C., and the drying time to 14 h.
6. The preparation method according to claim 2, characterized in that: The calcination method of the precursor in step six is: move the obtained precursor into a crucible, and then into a muffle furnace, set the temperature to 700° C., the calcination time to 4 h, and the heating rate to 4° C. / min.
7. Use of the solar-driven methanol-to-syngas catalyst according to claim 1 in solar-driven methanol-to-syngas.
8. The use according to claim 7, characterized in that: A 300W xenon lamp simulating sunlight was used as the light source in the reaction.
9. The use according to claim 7, characterized in that The reaction conditions of the solar-driven methanol-to-syngas reaction are: the reaction light intensity is 3.5-7.5W / cm under the condition of concentrated light. 2 , the reaction pressure is 1 atmosphere, and the methanol concentration is 5-24.5 mol / L.